Effectiveness of Wearable Technology in Monitoring Blood Sugar Levels in Diabetes Patients in Medan - Annisa Alsadilla Zahra; Yolanda Eliza Putri Lubis; Ica Yulianti Pulungan (Publikasi Indonesia, 2025)
Diabetes mellitus is a chronic disease that requires continuous monitoring of blood sugar levels to prevent serious complications. Wearable technology has emerged as an innovative solution for health monitoring, especially for people with diabetes. This study aims to evaluate the effectiveness of wearable technology in monitoring blood sugar levels in diabetes patients in Medan. The research employed a systematic literature review, analyzing scientific sources from PubMed, Google Scholar, ScienceDirect, and IEEE Xplore databases published between 2014 and 2024. Inclusion criteria encompassed studies on wearable technology for diabetes monitoring with clear methodologies, while exclusion criteria eliminated duplicates, irrelevant articles, or those with weak methodologies. From an initial 150 articles, 45 studies involving a total of 2,456 participants were ultimately analyzed. The results showed that wearable technologies—such as smartwatches and continuous glucose monitoring (CGM) devices—offer convenience in real-time monitoring, increasing patient compliance by 97%, lowering HbA1c by 0.8%, increasing time in range by 16%, and reducing hypoglycemia episodes by 55%. However, challenges persist, including measurement accuracy, FDA validation, high costs, and individual variability, all of which affect result consistency. Implementation in the Medan area remains limited due to economic and infrastructure factors. This study concludes that wearable technology holds great potential for improving the quality of life of people with diabetes, but further research is needed to validate its accuracy and reliability, along with policy support to enhance accessibility in Indonesia. The findings have significant implications for healthcare policy development, suggesting the need for government subsidies and insurance coverage to boost technology adoption rates among Indonesian diabetes patients, particularly in urban settings like Medan, where diabetes prevalence continues to rise